أحكام الضيافة من منظور مقاصد الشريعة وتطبيقاتها في مطار كوالالمبور الدولي الأول (KLIA 1) - Mohamad Zulkifli bin Abd Rahman (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This study aims to investigate hospitality services at the Kuala Lumpur International Airport 1 (KLIA 1). Specifically, it attempts to find out about hospitality in Islamic law, about hospitality services offered at the airport and about the extent of Maqasid al-Shari'ah (objectives of the Islamic law) verification in hospitality services practices at the airport. To achieve these objectives, appropriate research methods were utilised. The inductive method was used to gather information about hospitality and Maqasid al-Shari'ah from classic and modern texts. The survey method was also used to collect the data by distributing the questionnaire to the tourists who came to KLIA 1 as well as towards the foreign students and workers who have been staying in Malaysia for the past few years. The descriptive analytical method was then used to discuss the information collected from the texts and from the result of the questionnaire. This research concludes that the hospitality services at the airport achieve some objectives of Islamic law such as taysir (alleviation), cooperation and respecting human rights. The implementation of hospitality services that suits Maqasid al-Shari'ah plays a big role in attracting tourists as the Maqasid al-Shari'ah is based on fitrah which exists in every human.